Interview 12 - Abubakari, Yushawu
This file contains the interview notes with Cash Money. Cash Money (pseudonymized) is 29 years old. He graduated from the university 5 years again but decided to start scamming after two years without a job. “Cash Money” has been scamming for 3 years now. “Cash Money” is single with 13 siblings in a polygamous family. The interview was conducted outside the club where “Cash Money” spend time with his girlfriend